Mathematical Modelling of Shafts in Drives - Petr Hruby; Tomas Nahlik; Dana Smetanova (Communications - Scientific letters of the University of Zilina, 2018)
Propeller shafts of the vehicle's drive transmit a torque to relatively large distances. The shafts are basically long and slender and must be dimensioned not only in terms of torsional stress, but it is also necessary to monitor their resistance to lateral vibration.In the paper, a simple model (of the solved problem) is constructed by the method of physical discretization, which is evident from the nature of the centrifugal force fields' influence on the spectral properties of the shaft. An analytical solving of speed resonances prop shafts test model (whose aim is to obtain values for verification subsequently processed models based on the transfer-matrix method and the finite element method) is performed.